PREVALENCIA DE ENFERMEDAD ARTERIAL PERIFÉRICA CON BASE AL ÍNDICE TOBILLO/BRAZO EN PACIENTES CON DIABETES MELLITUS TIPO 2 - Díaz-Cruz Gonzalo; Velázquez-Tlapanco Jorge; Islas-Cortés Perla Berenice; Martínez-Martínez Martha Leticia; Camacho-Calderón Nicolás; Gallardo-Vidal Lilia Susana (European Scientific Journal, ESJ, 2014)
Theankle/branchialindex to diagnose peripheral artery disease (PAD) has beeen describe in the general population. Few studies have reported the prevalence and usefulness on this indicator in patients with DM2 with macroangiopathy. Objective: To determine the prevalence of PAD based on the ankle/branchial index in patients with DM2. Material and methods: cross-sectional design was conducted in patients with DM2, aged 50 years in a Unit of Primary Care at IMSS, Querétaro, Mexico.Variables analyzed: sociodemographic, metabolic control and vascular complications. The EAP was determined by the ankle/branchial index with 8MHz vascular doppler with pathological values between < 0.9 and > 1.3. Descriptive analysis with absolute and relative frecuencies and confidence intervals 95% was obtained with SPSS V20.Results:Of 241 patients, mean age 61.24±8.37 years and 65.6% were female. The global prevalence of PAD was 31.1%, predominantly mild form (26.6%). Of 75 patients with PAD, the mean age of 62.07±8.58 years, duration of DM2 12.83, BMI 31.90±4.93 kg/m2 HbA1c 8.39 ±1.80%, cholesterol194.99±38.26 mg/dl, triglycerides213.27±132.84 mg/dl.Of 83% were women, age 50-59 years (49%), with duration ≥ 10 years of DM2 (55%),overwight and obesity (92%), arterial hypertension (61%), intermitent claudication, diminished or absent pedial pulses (47%).HbA1c ≥7% (76%9, cholesterol ≥200mg/dl (48%), triglycrides ≥150mg/dl (71%), neuropathy(55%), vascular cerebral event (4%) and myocardial infarction (12%).Conclusions: the prevalence of PAD was 31.1%, predominantly in women over 10 years of evolution, uncontrolled DM2, dyslipidemia with abnormal pedal pulse palpation (decreased or absent) and intermitent claudication.